Multiple sulfur isotope constraints on sulfate-driven anaerobic oxidation of methane: Evidence from authigenic pyrite in seepage areas of the South China Sea - Lin, Zhiyong; Sun, Xiaoming; Strauss, Harald; Lu, Yang; Gong, Junli; Xu, Li; Lu, Hongfeng; Teichert, Barbara M.A.; Peckmann, Jörn (Geochimica et cosmochimica acta, 2017)
Multiple sulfur isotope signatures and secondary ion mass spectroscopy (SIMS) sulfur isotope compositions of pyrite from two seafloor sites (DH-CL11 and HD109) in seepage areas of the South China Sea were measured in order to study isotope effects of sulfate-driven anaerobic oxidation of methane (SO4-AOM). The multiple sulfur isotopes of pyrite reveal variable ranges for both sites (δ34S: between −44.1‰ and −2.9‰ for DH-CL11 and between −43.8‰ and −1.6‰ for HD109; Δ33S: between 0.02‰ and 0.17‰ for DH-CL11 and between −0.03‰ and 0.14‰ for HD109). SIMS analysis reveals an extreme variability of δ34S values (between −50.3‰ and −2.7‰ in DH-CL11; between −50.1 and 52.4‰ in HD109) for three types of pyrite: (1) framboids, (2) zoned aggregates with radial overgrowth surrounding a framboidal core, and (3) euhedral pyrite crystals. The synchronous changes of geochemical proxies (sulfate and methane concentrations, δ34Ssulfate and δ18Osulfate, δ34Spyrite, and pyrite content) at the sulfate-methane transition zone (SMTZ) at site DH-CL11 are interpreted to be induced by SO4-AOM under steady state conditions. In contrast, pyrite content and δ34S value fluctuations throughout core HD109 suggest that the sediment at this site was affected by multiple pyritization events during diagenesis. Multiple sulfur isotope signatures of early diagenetic pyrite (i.e., with low and high δ34S values, the latter above 315 cmbsf in DH-CL11; above 70 cmbsf in HD109) in the upper sediment column suggest that organoclastic sulfate reduction (OSR) and sulfur disproportionation generated the observed isotopic signatures. In contrast to the early diagenetic 34S depleted framboids, the higher SIMS δ34S values of overgrowth and euhedral crystals suggest a late diagenetic 34S enriched pool of dissolved sulfide derived from SO4-AOM at the current and paleo-SMTZs. Interestingly, pyrite resulting from SO4-AOM in the SMTZ at site DH-CL11 reveals a distinct pattern with higher Δ33S values, different from pyrite resulting from OSR and sulfur disproportionation. Therefore, paired δ34S and Δ33S values may allow to differentiate OSR and SO4-AOM, although a full understanding of the isotope effects associated with SO4-AOM is hampered by uncertainties on the actual electron transfer mechanism in the syntrophic SO4-AOM consortium.